Matter and spirit : early 21st century funeral urns for the quick and the dead - Coleman, Wendy (Michaelis School of Fine Art, 2017)
When I was twenty-five I married a farmer from the Eastern Cape. I gave up living in a city, and saw myself spending the rest of my life in the country, involved in the concerns of mixed stock farming in a semi-arid region of South Africa. My life changed utterly when I was thirty-two with the sudden and unexpected death of my husband. I became again a city-dweller, a teacher, with three young children. The circumstances of my life have forced me to confront the reality of death, and to wrestle with the nature of my relationships with people whom I love, both those alive and those dead. The untimely death of my husband forced upon me a realisation of mortality, and an understanding that every relationship has a beginning and an end. Each relationship one has determines a role for oneself, as daughter, mother, wife, widow, as well as a changing understanding of one's own identity. Prior to embarking on this MFA, I had been working with clay, and reading in the history of ceramics. From my reading it was evident that the making of objects in clay had long been associated with burial practices in cultures all over the world. As my interest in making really large clay vessels grew I came to see that in making these vessels I could place myself as an object maker within this long tradition. In so doing I could make urns - funeral urns in a sense - that could memorialise my own relationships to specific individuals. Obviously, these vessels are funeral urns in a metaphorical sense only as these pots will never actually be used as burial vessels. Metaphorically they seek to symbolise our changing nature as individuals and to celebrate the lives which they represent and my relationships with the people concerned. Clay is an earth material, and because I was using this material I also wanted to make a connection with the earth itself, and with the life of humankind upon the earth. A physical death signals a major change in patterns of relatedness, but our lives are filled with little deaths, with change and resurrection, as we move towards our own experience of physical death. In a broader sense then I wish these vessels to speak also of the nature of this changing world, both the physical world which over geological time endlessly "dies" and is "resurrected ", and of the world of personal relationships where we find ourselves, changing inhabitants of this changing world. St Paul, the early Christian apostle, in writing to the church at Corinth, expressed this notion when he said, "I die every day" (1 Corinthians 15:31). I have called this exhibition Early 21st century funeral urns for the quick and the dead. Seven of the urns memorialise individuals, some dead, most not, each of whom is important to me. Two speak of a broader inevitable connection with the land, and of the part we play within the context of the changing nature of the landscape itself. In so doing I have attempted to construct a memorial for those relationships important to me. The urns thus serve as repositories of memory, as physical constructs which speak of relationship. The death of another person can radically change one's status and identity: in my case from farmer 's wife to widow, from country person to city-dweller, and now, as I present this exhibition, it seems to me to represent the current stage in my changing notion of who I am, from farmer's wife to artist. Who knows what deaths and resurrections lie ahead for us all?